Where they create Japan : creative studios shot by Paul Barbera - Barbera, Paul, ....-; Hasegawa, Kanae, ....- (Amsterdam : Frame, 2016)
Photographer Paul Barbera presents his next volume in the Where They Create series – this time with a different approach, by exploring the theme of his series through geographical locales – not just physically but also spiritually, as ‘place' is a very fluid concept in today's global world. Reinvigorated by his first visit to Japan in five years, he makes this metropolis the starting point of this new volume of photographs. Through the lens of creative spaces, Barbera chronicles his journey as he uncovers how contemporary Japanese design, art and creative thinking, has influenced and inspired the world (and vice versa). Barbera's search is simple and clear: he only visits the studios of people whose work he loves and admires, who have inspiring spaces. For this book, Barbera chose 30+ studios which form a diverse selection of his work. Featured are media companies and creatives, as well as artists, architects, illustrators and designers from all over Japan. In addition to all these photos, descriptions of the spaces by the owners of the studios are included. Interviews with these creators reveal the inner workings of these creatives, discovering how their daily environment